Examination of the organizational frameworks of sports enterprises in the light of good german practices - Bácsné Bába, Éva (Applied Studies in Agribusiness and Commerce, 2015)
In Hungary, with respect to the organizational issues associated with sports, there has occurred the demand for clarifying structural forms. The domestic development of sports raises the question in which fields the association-based sports model can be sustained, and operated further, and where organizational structures aligned with business models are viable. This article has described an example from German professional football, i.e. given an overview of the operation of Borussia Dortmund as a potential form for the enterprise and organizational solution. The strength of the demonstrated model is that the pursuance of business activities that cannot be or can be just hardly handled in the environment offered by associations is transferred to a setting dominated by economic conditions, whereas self-regulating civil values are not lost either, because the association remains the “parent company”.